The sports concussion picture: fewer `pixels`, more HD - Patricios, J. S.; Makdissi, M. (British Journal of Sports Medicine, 2014)
Current concussion scrutiny: In contrast to the "whole picture" described by Salman Rushdie, the media attention that concussion is currently receiving resembles a series of "pixels". Not only journalists but coaches, athletes, parents and even medical colleagues often appear to focus on only one facet of the intricate picture that makes up the composite concussion portrait. Examples of "pixels" include computerised cognitive tests, Rugby's pitch side suspected concussion assessment (PSCA) and chronic traumatic encephalopathy (CTE). Each of these topics is often scrutinised outside of the context of many other significant aspects of the concussion picture. CTE is one of the SEM's "hot topics" and the concussion strategies incorporated in collision sport are under increased scrutiny; in this edition of BJSM we provide updates on both.